Supply Chain Management in the Sphere of Household Economies in the Modern Economy of Russia - Lilia MirgaziyanovnaYusupova; Irina Arkadevna Kodolova; Tatyana Viktorovna Nikonova; Madina Irekovna Agliullina (International Journal of Supply Chain Management, 2019)
Abstract- Despite the fact that the terms "household finance", "individual finance", â€œsupply chain strategyâ€ and "personal finance" are recently found in the scientific literature and statistical studies quite often, their place and role in the financial system of the country and in the life of the population are not yet sufficiently visible and these terms need to be clarified. In modern Russia households direct certain share of their income to savings, but only if there are effective communications with the financial market, those savings can become significant sources of investment that are needed by any government. The article concluded that current savings of Russian population cannot be recognized as full â€“ valued free resources that can be directed to investment due to certain problems.